Direct comparison of liquid‐based and smear‐based cytology with and without rapid on‐site evaluation for fine needle aspirates of thoracic tumors. Issue 5 (8th February 2016) - Mfokazi, A.; Wright, C.A.; Louw, M.; Von Groote‐Bidlingmaier, F.; Schubert, P. T.; Koegelenberg, C. F. N.; Diacon, A. H.
Abstract : Background: Liquid‐based cytology (LBC) and rapid on‐site evaluation (ROSE) are proposed to improve the quality of fine needle aspirates (FNA) and their diagnostic yield compared with conventional smear cytology (CSC). This prospective study directly compared outcomes of sonar‐guided FNA of thoracic tumors supported by LBC, CSC, or CSC with ROSE . Methods: Three aspirates each for both LBC and CSC with separate 22G spinal needles in a randomized, alternating sequence during 64 transthoracic FNA of thoracic tumors were collected. Smears were prepared by cytology staff on site but evaluated with ROSE only when all six samples had been collected. If no diagnostic material was found on the first three CSC additional needle passes guided by ROSE were performed . Results: Final diagnoses were non‐small cell lung cancer in 50 (78.1%), small cell lung cancer in 11 (17.2%), mesothelioma in 1 (1.6%), and inflammation in 2 cases (3.1%), respectively. LBC and CSC were diagnostic in 42 (65.6%) and 49 (76.6%) cases, respectively (P = 0.039), with both methods diagnostic in 41 cases (64.1%). Fifteen cases (23.4%) remained undiagnosed following three passes for CSC but 9 (14.1%) of these were diagnosed using FNA and ROSE with a total yield of 58 cases (90.6%; P < 0.001) . Conclusion: The diagnostic yield of transthoracic FNA submitted for LBC is significantly lower than with CSC when slides are prepared professionally. ROSE significantly increases the yield of transthoracic FNA . Diagn. Cytopathol. 2016;44:363–368. © 2016 Wiley Periodicals, Inc.